2018
DOI: 10.1037/fsh0000374
|View full text |Cite
|
Sign up to set email alerts
|

To go or not go: Patient preference in seeking specialty mental health versus behavioral consultation within the primary care behavioral health consultation model.

Abstract: Introduction: Much of behavioral health care takes place within primary care settings rather than in specialty mental health settings. Access to specialty mental health care can be difficult due to limited access to mental health providers and wait times to receive mental health care. The purpose of this study is to determine patient satisfaction with behavioral health consultation visits that take place within the context of the primary care behavioral health consultation model. Patient likelihood to seek out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…For example, cancer survivors tend to prefer specialist follow-up, [21][22][23] while limited research indicates that patients with mental illness may prefer to access their own GP practice. 24,25 A survey relating to epilepsy services found that while younger patients and those with severe epilepsy preferred secondary care, older patients preferred to receive care from their GP. 26 Patients in this study, who tended to be older (mean age 67 years), expressed a strong preference for having their LUTS treated in primary care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, cancer survivors tend to prefer specialist follow-up, [21][22][23] while limited research indicates that patients with mental illness may prefer to access their own GP practice. 24,25 A survey relating to epilepsy services found that while younger patients and those with severe epilepsy preferred secondary care, older patients preferred to receive care from their GP. 26 Patients in this study, who tended to be older (mean age 67 years), expressed a strong preference for having their LUTS treated in primary care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Patients in this study indicated a strong preference for their symptoms to be managed in primary care. Given that preference for primary versus secondary care appears to vary between different patient groups, [21][22][23][24][25][26] it would be interesting to further explore the effect of patient characteristics on treatment preferences.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…For some, receiving mental healthcare from primary care providers may be preferable to and more feasible than specialized care within behavioral health clinics; in fact, prior research demonstrates that military spouses receive more mental health care outside of mental health settings as compared to service members, irrespective of service branch and diagnosis, and that this care is largely delivered by primary care providers in primary care settings (Center for Naval Analyses, 2010; Ogbeide et al, 2018). Though seeking mental healthcare through a primary care provider may reduce some potential barriers to care (e.g., wider availability of primary care providers, less wait time, potential reduction of stigma), the limited training in specialized psychological services received by many primary care doctors may affect the quality of mental healthcare received.…”
Section: Discussionmentioning
confidence: 99%
“…The PCBH team consists of a PCP and an Integrated Behavioral Health Consultant (BHC) who is traditionally either a Psychologist or Licensed Clinical Social Worker “embedded” in the clinic and is a member of the primary care practice team. Implementation of the PCBH model is ahead of the evidence supporting outcomes, but several studies have shown promise in increasing both access to and the satisfaction of consumers who have received integrated behavioral health care as part of their primary care visit (Ivey et al, 2017; Kaltman et al, 2011; Lockeman et al, 2017; Possemato et al, 2018; Ramanuj et al, 2019) as well as an increase in PCP satisfaction (Hine et al, 2017; Ogbeide et al, 2018).…”
Section: Overview Of Integrated Behavioral Health and The Pcbhmentioning
confidence: 99%